PENGARUH PERUBAHAN TINGKAT SUKU BUNGA DAN INFLASI TERHADAP PEMBIAYAAN BANK UMUM SYARIAH (Studi Kasus Pada Bank Umum Syariah Tahun 2020) - Imam Azizuddin; Tazkiyah Rasyidah (Jurnal Ekonomi Syariah Pelita Bangsa, 2022)
The study is purpose to know the effect of inflation and interest rates on financing at islamic commercial banks registered with financial services authorities for period in 2020. In this study used the quantitative method, secondary data and time series. The data obtain from the reports published by Indonesias Statistics agency and Bank Indonesia included for sample in this study at 2020. This study were 12 data. The technique was used for this study is multiple linier regression using the Eviews 10 application program. The results of the analysis proses that inflation have negatively affects not significant while interest rates have negative and significant effect on financing at Islamic Commercial Banks. And the result of the silmutan test (F-Test) stated the inflation and interest rates together or simultaneous have a significant influence on financing at Islamic Commercial Banks.